2021
DOI: 10.1111/iju.14515
|View full text |Cite
|
Sign up to set email alerts
|

Predictive score for vesicoureteral reflux in children with a first febrile urinary tract infection

Abstract: Abbreviations & Acronyms AUROC = area under the receiver-operating characteristic curve CI = confidence interval CRP = C-reactive protein IQR = interquartile range LHR+ = positive likelihood ratio ROC = receiver-operating characteristic US = ultrasonography UTI = urinary tract infection VCUG = voiding cystourethrography VUR = vesicoureteral reflux WBC = white blood cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Of the 29 included studies, 9 studies were published between 2000 and 2010, whereas 20 studies were published between 2011 and 2022 (Table). Nineteen studies were retrospective, and 10 studies were prospective cohorts. No randomized clinical trials or cohort studies compared kidney ultrasonography with first febrile UTI vs targeted strategies (eg, deferring until second febrile UTI).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 29 included studies, 9 studies were published between 2000 and 2010, whereas 20 studies were published between 2011 and 2022 (Table). Nineteen studies were retrospective, and 10 studies were prospective cohorts. No randomized clinical trials or cohort studies compared kidney ultrasonography with first febrile UTI vs targeted strategies (eg, deferring until second febrile UTI).…”
Section: Resultsmentioning
confidence: 99%
“…The study sample size ranged from 66 to 820 children (median, 300 children). Of the 21 studies that reported the causative bacteria, Escherichia coli was the main causative bacteria (median, 86% [range, 67%-96%]). Fifteen of 25 studies that included data on kidney ultrasonography timing reported performing ultrasonography during the hospital admission or within a week after diagnosis of UTI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations